Communication theories perspectives, processes, and contexts - Miller, Katherine 1959- (McGraw-Hill, 2002)
Provides students with a comprehensive discussion of influential theories in communication. Emphasizing theories developed by communication scholars, this book also includes theories developed outside the field that have strongly influenced the work of communication scholars.